Relations Between Religion and Multicultural Society - Makmur, Zulkifli; Kango, Andries (Jurnal Kajian Manajemen Dakwah, 2023)
This research aims to provide a more detailed picture regarding the causes of multicultural conflict, the positive and negative impacts of religion in the multicultural concept and the forms of synergy between religion and multicultural society in Indonesia. This research will use the literature study method. The collected data will be analyzed using a literature review to identify the main themes and da'wah writing strategies used by Islamic boarding schools in their campaigns. The research results found that multicultural conflict can occur if segmentation arises into groups in society. Religion in multicultural societies can be used in negative and positive ways. Apart from that, the synergy of religion and multicultural society can be realized by reinterpreting orthodox religious doctrines, dialogue and using religion as a mediation suggestion for cultural differences and conflict resolution in society